Prevalence of methotrexate intolerance among patients with rheumatoid arthritis in Erbil city using methotrexate intolerance severity score - Zhala Kakamin Mawlood; Dashty Abbas Albustany (Advanced Medical Journal)
Background and objectives:  Rheumatoid arthritis is classified as an autoimmune disease characterized by inflammation of the joints and membranes surrounding the joints.The aim of this study was to find the frequency of methotrexate intolerance among rheumatoid arthritis patients and to detect factors contributing to intolerance.